PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THIRNK PAIR SHARE (TPS) DAN PEMAHAMAN KONSEP DASAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA DI KELAS XI IPA SMA NEGERI 1 MANOKWARI - Aponno, Josephina Paulina; Lumbu, Albert (Jurnal Ilmu Pendidikan Indonesia, 2015)
Have been determine the effect of the learning model cooperative TPS on student learning outcomes and influence the understanding of student learning outcomes as well as the influence of the type of learning model cooperative TPS and understanding of the learning outcomes students. This study uses the experiment method kuantitaf pre-experimental designs (Nondesigns) involving 30 students of SMA Negeri 1 Manokwari class XI Science academic year 2013/2014. Data analysis using correlation and regression analysis. Results of data analysis found the magnitude of the effect between the model pembeljaran simultaneous cooperative TPS (X1) andinfluence the understanding (X1) to the student learning outcomes (Y) 0,757 for the relatively strong. Where as contributions together (simultaneously) variables X1 and X1, Y = R x 100% or 0,7572 x 100% = 57,3% and the remaining 42,7% is determined by other variables. the size of the learning outcomes can be predicted by the regression equation. Y=-0,522 + 0,499X1 + 0,372X2. Keywords: Cooperative Learning Model Think Pair Share, Understanding, Learning Outcomes, Probability